The Effect of Work from Home, Work Life Balance, and Work Motivation on Job Satisfaction and Their Impact on the Performance of Non-Lecturer Education Personnel at Pertamina University Jakarta - Suryono Efendi; Anggit Purwanto; Edi Sugiono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine the effect of Work From Home, Work Life Balance, and Work Motivation on Job Satisfaction and Its Impact on the Performance of Non-Lecturer Education Personnel and for information, input, and study materials for Non-Lecturer Education Personnel at Pertamina University Jakarta Independent Variable: Work From Home (X1), Work Life Balance (X2) and Work Motivation (X3). The dependent variable is Job Satisfaction (Y1) as an intervening variable, its impact on performance (Y2). The research approach used is secondary data processing as a result of Job Satisfaction of Non-Lecturer Education Personnel. The model was analyzed using AMOS statistical software version 22. The data processed were 23 samples from 120 participant population data with purposive sampling. This study finds that Job Satisfaction has a significant and significant effect on the Performance of Non-Lecturer Education Personnel.